Efficient gene editing in adult mouse livers via adenoviral delivery of CRISPR/Cas9. Issue 21 (19th September 2014) - Cheng, Ranran; Peng, Jin; Yan, Yonghong; Cao, Peili; Wang, Jiewei; Qiu, Chen; Tang, Lichun; Liu, Di; Tang, Li; Jin, Jianping; Huang, Xingxu; He, Fuchu; et al.
Abstract : We developed an adenovirus‐based CRISPR/Cas9 system for gene editing in vivo. In the liver, we demonstrated that the system could reach the level of tissue‐specific gene knockout, resulting in phenotypic changes. Given the wide spectrum of cell types susceptible to adenoviral infection, and the fact that adenoviral genome rarely integrates into its host cell genome, we believe the adenovirus‐based CRISPR/Cas9 system will find applications in a variety of experimental settings. Abstract : Adenoviral delivery of CRISPR/Cas9 produces efficient gene editing in cultured cells. Effective gene knockout in the adult mouse liver via adenoviral delivery of CRISPR/Cas9. The gene editing in the liver is stable over long term and after extensive liver tissue regeneration.